THE DISSOLUTION MECHANISMS OF WATER IN SILICATE MELTS; A SYNTHESIS OF RECENT DATA - Kohn S.C. (My University, 2000)
Dissolved water has significant effects on the physical and chemical properties of silicate melts. Some of the different approaches towards understanding these effects are reviewed here. Spectroscopic measurements on hydrous glasses quenched from melts provide good models for the structure of the melts at the glass transition temperature (T-g). Such measurements suggest that the mechanism of dissolution of water in silicate melts varies strongly with the bulk composition. In particular framework aluminosilicate compositions seem to have very different dissolution mechanisms from Al-free compositions. The water speciation reactions are temperature dependent, with some of the molecular water which is present in glasses at room temperature being converted to hydroxyl at high temperatures. This conversion probably occurs only above T-g. Data on the kinetics of the speciation reaction and the dynamics of microscopic processes in hydrous silicate melts are also discussed. Finally some important aims of future work on hydrous silicate melts are suggested.